Correlation analysis of thyroid function and vitamin D levels in patients with type 2 diabetes - Wu, Lizhen; Liang, Bo; Lin, Ruhai; Fu, Zhenfei; Huang, Huibin; Zhou, Jingxiong (Frontiers in Endocrinology, 2025)
BackgroundThis study investigated the association between vitamin D status and thyroid function in 1,805 adults with type 2 diabetes mellitus (T2DM) treated at a tertiary hospital between 2018 and 2024. We analyzed demographic, metabolic, and thyroid function parameters to determine whether vitamin D levels influence thyroid dysfunction in this population.MethodsPlasma 25-hydroxyvitamin D, thyroid hormones (FT3, FT4, TSH), and autoantibodies (TPOAb, TGAb, TRAb) were measured using electrochemiluminescence. HbA1c was assessed via HPLC. Statistical analyses included Spearman correlation and logistic regression to evaluate relationships between vitamin D levels (categorized as deficient < 20 ng/mL, insufficient 20-29.9 ng/mL, and sufficient ≥ 30 ng/mL) and thyroid disorders.ResultsVitamin D sufficiency (≥ 30 ng/mL) was positively associated with male sex (OR=2.52), older age (OR=1.05), and higher FT3 (OR=1.28), while inversely linked to elevated triglycerides (OR=0.68) and HbA1c (OR=0.88). Hyperthyroidism showed significant associations with low vitamin D (OR=1.07) and younger age (OR=0.93), whereas hypothyroidism correlated with aging (OR=1.07) and high cholesterol (OR=1.07). No significant relationships were found between vitamin D and thyroid autoimmunity.ConclusionsVitamin D deficiency is independently associated with hyperthyroidism and subclinical hyperthyroidism in T2DM patients, suggesting a potential role in thyroid dysregulation. These findings support screening for vitamin D deficiency in diabetic individuals with thyroid dysfunction.